SOSIALISASI PENGGUNAAN TED TALK VIDEO DALAM MENGEMBANGKAN KEMAMPUAN SPEAKING - Suparlan, Suparlan; Masyudi, Masyudi (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
The purpose of this community service is to develop the Speaking skills of the second class of the students of SMK Negeri 3 Gunungsari Lombok Barat through the use of TED Talk Videos. Listening to TED Talks Video can provide an overview of content structure, make content understanding more optimal, also facilitate the teaching and learning process in more depth, and make learning more stimulating because it applies new models in learning. Through the TED Talk Video, we can learn about the ability to speak effectively in public and learn how intonation, body movements, eye contact, and control awareness without anxiety, can boost students' self-confidence. Conduct socialization and education regarding efforts to develop speaking skills by using TED Talks Videos as a solution that can be used to overcome the English-Speaking Skill constraints of students at the[i] second class of SMK Negeri 3 Gunungsari Lombok Barat.